Thermogravimetric investigations of cream with minoxidil - I. V. Gnitko; I. I. Berdei; V. V. Gladishev; B. S. Burlaka (Zaporozhye State Medical University, 2016)
Minoxidil is one of the most effective and modern medications, which is used in modern trichology for hair growth stimulation in case of androgenic and other forms of alopecia. Clinical effect of this substance is caused by the intensification of metabolic processes in the skin due to intensification of microcirculation. For local application domestic dermatology uses imported minoxidil medicines in form of alcohol-water lotions and aerosols. The use of semisolid dosage form with minoxidil for external administration will allow to increase its efficacy and will widen the arsenal of domestic pharmacotherapeutic agents for hair growth stimulation. Rational composition of minoxidil semisolid dosage form for external use with 2% of active substance has been developed at the Department of Medicinal Preparations Technology, Zaporozhye State Medical University as a result of complex physical-chemical, microbiological and biopharmaceutical investigations. The aim of this work is the study of thermal treatment effects of cream-mask with minoxidil for external use over the temperature range, which is used in technological process of this dosage form manufacturing. Materials and methods. Cream with 2% of minoxidil on the emulsion base and its excipients have been used as the object for the thermogravimetric investigations. Thermogravimetric analysis has been carried out on the derivatograph «Shimadzu DTG-60», Japan, with the platinum and platinum-rhodium thermopair with samples' heating in aluminium crucibles from 25 to 200ºС. Results. According to thermogravimetric experimental data minoxidil is a thermal stable substance from 26 to 240ºС. During experimental process insignificant endothermic effect was determined at 191,72ºС. However the mass of the example to the end of experiment practically didn't change (decrease on 0,32%). Thermal effects on the derivatogram of minoxidil emulsion cream match with thermal effects of the base components and this fact indicates absences of chemical interact between active substance and excipients in semisolid dosage form. Conclusions. Preparation of the cream-mask with 2% of minoxidil in the temperature range, which is used in technological process of creams on the emulsion base (60-80ºС) doesn't lead to destruction of the components in the present dosage form.